mRNA-1273 COVID-19 vaccine induces CD4+ T-cell responses among solid organ transplant recipients - Girard, Bethany; Figueroa, Amparo L.; De Rosa, Stephen C.; McElrath, M. Juliana; Azzi, Jamil R.; Stolman, Dina; Siangphoe, Uma; de Windt, Elizabeth; Miller, Jacqueline M.; Das, Rituparna; Priddy, Frances (Frontiers in Immunology, 2025)
BackgroundCell-mediated immunity may provide durable protection against severe COVID-19, including among solid organ transplant recipients (SOTRs). This exploratory analysis in the open-label phase 3b trial evaluated cell-mediated immunity of mRNA-1273 in a subset of participants (59 kidney and 33 liver SOTRs; 12 immunocompetent participants).MethodsIn Part A, SOTRs received three 100-µg doses of mRNA-1273; immunocompetent participants received two doses. In Part B, an additional 100-µg dose was offered ≥4 months after the primary series. SARS-CoV-2 spike (S) protein-specific T-cell responses were measured by intracellular cytokine staining and polyfunctionality analyses.ResultsThe primary series and additional dose of mRNA-1273 induced S protein-specific CD4+ T-cell responses exhibiting a Th-1-biased profile in both SOTRs and immunocompetent participants; however, response rates and magnitudes were lower among SOTRs. S protein-specific Th-2 CD4+ T-cell responses were below those observed for Th-1; CD8+ T-cell responses were not as robust among SOTRs compared with immunocompetent participants. Kidney SOTRs received multiple immunosuppressants and had lower cell-mediated immunity responses than liver SOTRs. Polyfunctional responses exhibited Th-1 cytokine signatures with ≤5 functional markers reported in SOTRs and immunocompetent participants.ConclusionOverall, a three-dose mRNA-1273 primary series elicited Th-1-biased CD4+ T-cell responses among SOTRs that were improved with an additional dose.Clinical trial registrationhttps://beta.clinicaltrials.gov/study/NCT04860297?term=NCT04860297%20&rank=1, identifier NCT04860297.